Community Norms and Organizational Practices: The Legitimization of Wage Arrears in Russia, 1992-1999 - John S. Earle; Andrew Spicer; Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2004)
What role do community norms play in the diffusion and persistence of new organizational practices? We explore this question through an examination of the widespread practice of wage arrears, the late and non-payment of wages, in Russia during the 1990s. Existing research on wage arrears most often examines this practice as a means of flexible wage adjustment under difficult economic conditions. We develop an alternative theory that explains wage arrears through their acceptance as a legitimate form of organizational behavior within local communities. Our empirical analysis finds some support for the neoclassical position that wage arrears reflect adjustment to negative shocks, but this perspective fails to account for a number of important facts, including a high level of arrears among apparently successful firms. In contrast, our results find strong support for the institutional perspective. The statistical analysis demonstrates powerful and robust community effects both in firm adoption of this practice, controlling for firm performance, liquidity, and fixed firm effects, and in workers? reaction to arrears, through their quit (exit) and strike (voice) behavior.
Keywords: P31; O17; J30; P37; L14; A12; B52; A14; 330; institutions; norms; legitimacy; arrears; organizational practices; sociology; Russia; Lohn; Verbindlichkeiten; Lohnflexibilisierung; Unternehmenskultur; Institutionalismus; Soziale Werte; Schätzung; Russland; Lohnrückstände